Estudo de impacto de vizinhança: um instrumento para a melhoria da qualidade de vida na zona sul da cidade de João Pessoa – PB. - Soares , Wender Imperiano Ribeiro. (2013)
The current world population focuses, in its majority, in the urban areas, as indicates DSNI (Demographic Studies National Institute), that around 3,3 billion of people, that is 51% of the world population lives in the urban areas. In all the world, especially in the so called developing countries, since it is in these nations where the disparity is an eye-catching, that the idea of remodelling the urban environment was born, providing a more just or less unequal society. Brazil situation is not an exception and after years of discussing, comes to light the Law 10.257/2001, that regulates the articles 182 and 183 of CF/88, that discusses about the Urban Politics, bringing a list of instruments of the urban reform and among them, there is the Study of Neighbourhood Impact (SNI), that aims an environment and socioeconomic assessment that can cause impacts in the urban areas, aiding in the achievement of sustainable cities. Focusing on the so called South Zone of the city of João Pessoa – PB, the present study aims to observe and understand the spatial reproduction that locality and confront the basic precepts of SNI, so for verifying the quality of life of the resident population that area, whether it comes or not suffering negative impacts with the intense modification of the environment in which they live.